Learning and Price Discovery in a Search Market. (9th June 2017) - Lauermann, Stephan; Merzyn, Wolfram; Virág, Gábor
Abstract: We introduce learning into an otherwise standard two-sided search-and-bargaining market. There is uncertainty about the price distribution due to uncertainty about an underlying exogenous state of relative demand: in the high state, buyers are on the long side; otherwise, they are on the short side. In equilibrium, prices are on average higher in the high state. Individual agents learn about the distribution while searching. Agents typically start out by experimenting with a tough bargaining position—buyers may initially insist on a low price and sellers on a high price. After successive failures to trade, agents become increasingly pessimistic about the market conditions and soften their bargaining stance. When frictions are small, equilibrium transaction prices are approximately market clearing, despite aggregate demand being unknown. Thus, the search-and-bargaining procedure enables price discovery in a decentralized market.